The manufacture of organic carbonate-poly(methyl ethylacrylate) nanowebs with thermal buffering effect - Önder Karaoğlu, Emel; SARIER, NİHAL; ARAT, REFİK (Elsevier Science Bv, Po Box 211, 1000 AE Amsterdam, Netherlands, 2017)
In this study, novel nanowebs provided with thermal buffering properties were developed via coaxial electro-spinning. Environmental friendly and nontoxic dialkyl and dialkenyl carbonates (DACs), namely, didecyl carbonate, didodecyl carbonate, ditetradecyl carbonate, dihexadecyl carbonate, dioctadecyl carbonate and dioleyl carbonate were synthesized from their fatty alcohols based on carbonate interchange reaction. Then the DAC-PMEA nanowebs were produced using 10-50 w% DAC in 3:1 chloroform-ethanol solution as core and 15 w% poly(methyl ethylacrylate) (PMEA)in ethanol as shell by coaxial electrospinning. The SEM images of the nanowebs presented randomly oriented, ultrafine fibers identified with smooth surfaces, continuous and cylindrical shapes. The nanowebs were able to provide considerable enthalpies (40-100 J g(-1)) during their repeated phase changes, up to hundred heating-cooling cycles, corresponding to 52-92% efficiencies obtained from electrospinning. These shape stabilized, lightweight DAC-PMEA nanowebs showed a significant potential for the dynamic thermal insulation applications across various industries, especially for the protection of temperature sensitive materials.
Keywords: Phase change material; Coaxial electrospinning; Organic carbonate; Nanoweb; Thermal properties; Phase-Change Materials; Energy Storage; Composite Fibers; Pcm Emulsions; Ice-Cream; Fabrication; Carbonates; Food; Encapsulation; Nanofibers